KEPENTINGAN TIONGKOK MENGELUARKAN HAK VETO TERHADAP RESOLUSI DEWAN KEAMANAN PBB TENTANG KONFLIK SURIAH TAHUN 2012 - Nurfazlina, Siti; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research explains Tiongkok’s interests in issuing a veto against the UN Security Council resolution drafts on syria conflict in 2012. The conflict in Syria is one of the impact of the Arab spring. The conflict in Syria is a civil conflict that demands the Syrian president to step down. In the face of the civil conflict, the Syrian government often used military and armed forces that resulted in the loss of life of many civilians. Seeing the Syrian government action taken in the face of this conflict, the UN Security Council drafted resolutions on Syria to help resolve the internal conflicts. This research will discuss about Tiongkok’s interest in syria conflict so that Tiongkok issued a veto on the UN Security Council resolution. This research applied realisme perspective, Diplomacy theory and Nation-State analys. Realism perspective believes that main actor in international relations is a country. This research collected data from books, journals and websites which discusses the existence of Tiongkok interest in Syria Conflict and Tiongkok reasons issued a veto of UN security Council resolution in Syria conflict. This research found that Tiongkok has a economic and political interests in Syria.Keywords : Syria Conflict, Veto, UN Security Council, Resolutions